PTU-018 Analysis of bedside predictors of survival following TIPSS for refractory ascites in a regional centre. (June 2019) - Lachlan, Neil; Gillespie, Ruth; Barclay, Stephen; Forrest, Ewan; Stanley, Adrian
Abstract : Introduction: Prognosis in refractory ascites (RA) is poor and patient selection for TIPSS challenging. In 2011 Bureau et al identified Bilirubin <50 umol/L and platelet count >75 x 10 9 /L, the 'Bureau Criteria' (BC), to be predictive of survival post-TIPSS in 73% vs 31% in those out with the BC. Age over 65 yrs has also been considered a risk factor for poor outcome post-TIPSS. In this study we analyse the BC and age in a Glasgow cohort. Methods: Retrospective analysis of all patients undergoing TIPSS for RA between 2011–17 in Glasgow was undertaken. Baseline pre-TIPSS data was recorded and actuarial survival at 1 year assessed in 2 groups: those that did, and did not, fulfil the BC. Age >65, in isolation of other variables, with 1 year survival was also assessed. Results: 31 patients underwent TIPSS for RA in this 7 year period. Liver disease aetiology was alcohol (± Hepatitis C) in 87%. At baseline pre-TIPSS the mean age was 58.1 yrs (range 36–79), MELD 12.5 (7–21), Bilirubin 30 (5–127) and Platelet count 161 (15–364). 22 patients fulfilled the BC, 2 were transplanted within 1 year of TIPSS. None of the 9 non-BC patients were transplanted. Actuarial 1 year survival was 14/22 (63.6%) in the BC group and 3/9 (33.3%) in the non-BC group. Of the 6 patients over 65 yrs, all - except 1 who was transplanted - died within 1 year of TIPSS, this was despite 5 of those 6 fulfilling the BC. Mean transplant-free survival in patients over 65 yrs was 4.1 months (Range 0.75–8 months). Of those that were both <65 yrs and fulfilled BC, 1 year actuarial survival reached 70.5%. Conclusion: The combination of bilirubin <50 and platelet count >75 is predictive of survival post-TIPSS for refractory ascites in our regional cohort and these outcomes are similar to those in the published literature. However, regardless of the bilirubin and platelet count, great caution should be exercised when considering TIPSS in any patient over the age of 65.